A Review of the Synthesis, Properties, and Applications of 2D Materials. (9th May 2022) - Shanmugam, Vigneshwaran; Mensah, Rhoda Afriyie; Babu, Karthik; Gawusu, Sidique; Chanda, Avishek; Tu, Yongming; Neisiany, Rasoul Esmaeely; Försth, Michael; Sas, Gabriel; Das, Oisik
Abstract: In the modern age of nanotechnology, the discovery of graphene has opened up the way to study and develop of several novel 2D materials. The unique physical and chemical properties of 2D materials have enhanced their research, making them superior to the commercial bulk materials used in various applications. Efforts have been made in the current study to present an overview of the intrinsic properties of these materials. Furthermore, synthesis and applications are also reviewed and discussed. Finally, the future outlook of 2D materials is discussed to enhance the research and performance of these materials, which can result in broader applications benefitting the electrical and electronics industries and society. Intensive research into 2D materials is expected to lead to the discovery of new materials with enhanced properties that will benefit the industry and society at large. Abstract : 2D materials have unique intrinsic properties. The properties of 2D materials are tunable. Layer size produces significant variation in properties. Ductile failure in 2D materials is very rare. Transition metal‐dichalcogenides are superior to graphene.